INVESTIGATION OF SOCIAL AND PSYCHOLOGICAL FEATURES OF ADOLESCENT AGGRESSION DURING WAR (Psychology Travelogs, 2025)
The study addresses a significant socio-pedagogical problem – adolescent aggressive behavior – particularly during wartime conditions. Adolescence is a critical developmental stage marked by psychophysiological changes, heightened emotional instability, and limited emotional self-regulation skills, all of which increase the risk of aggressive behavior. The stressors associated with war, such as heightened anxiety, fear, trauma, and loss, exacerbate these tendencies, making adolescents particularly vulnerable to destructive behaviors. Additionally, shifting social roles and adult behavioral models observed during wartime can further shape aggressive attitudes in adolescents.The study emphasizes the importance of examining these social-psychological features to develop effective psychological support and aggression prevention programs. These efforts aim to stabilize adolescents' emotional states, enhance constructive interaction skills, and mitigate the traumatic effects of war. While previous research extensively explores the nature and causes of human aggression, the wartime context highlights unique challenges that demand further attention, especially among adolescents.The study draws on foundational theories of aggression from researchers such as L. Berkowitz, D. Richardson, and A. Bandura, as well as more recent investigations into age and gender-specific patterns of adolescent aggression. These works identify key determinants of aggression, including familial upbringing, media influence, social support, and individual psychological traits. However, contemporary psycho-pedagogical practices still lack a comprehensive approach to addressing adolescent aggression, particularly in wartime.The study underscores the need for a comprehensive, targeted approach to reduce adolescent aggression. By addressing internal and external determinants, fostering emotional resilience, and promoting constructive behaviors, such interventions can help adolescents navigate the challenges of wartime and mitigate the long-term consequences of aggressive behavior.
Keywords: aggression; aggressiveness; aggressive manifestations; aggressive behavior; adolescence; socio-psychological characteristics